2014
DOI: 10.1021/am504086x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transitions in Asymmetric Poly(styrene)-block-Poly(lactide) Thin Films Induced by Solvent Vapor Exposure

Abstract: Successive structural transitions in thin films of asymmetric poly(styrene)-block-poly(lactide) (PS-PLA) block copolymer samples upon exposure to tetrahydrofuran (THF) vapors have been monitored using atomic force microscopy (AFM) and both in situ and ex situ grazing incidence small-angle X-ray scattering (GISAXS). A direct link was established between the structure in the swollen state and the morphology formed in the dried state post solvent evaporation. This was related to the high incompatibility between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…40,41 GISAXS (grazing incidence small-angle X-ray scattering) studies have characterized the average morphology as a function of annealing time for several BCP systems. 25,[42][43][44][45][46] These experiments showed that ordering began during the swelling stages of the thin film and that the final structures were independent of the casting method. If films are swollen too much or if the BCP has a low w, the order is lost at a critical swelling thickness during the anneal as the system exceeds the ODT.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…40,41 GISAXS (grazing incidence small-angle X-ray scattering) studies have characterized the average morphology as a function of annealing time for several BCP systems. 25,[42][43][44][45][46] These experiments showed that ordering began during the swelling stages of the thin film and that the final structures were independent of the casting method. If films are swollen too much or if the BCP has a low w, the order is lost at a critical swelling thickness during the anneal as the system exceeds the ODT.…”
Section: Introductionmentioning
confidence: 93%
“…The pre-stage determines initial film thickness D 0 , but assuming a thermodynamic equilibrium is reached during annealing, the memory of the as-cast morphology is lost. 46 Swelling refers to the ingress of solvent into the thin film and the resulting increase in film thickness, and quenching or deswelling refers to solvent egress and the resulting decrease in film thickness. The film is usually assumed to collapse in the out-of-plane direction, preserving in-plane microdomains.…”
Section: B Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations